Biochar-based electroanalytical materials: Towards sustainable, high-performance electrocatalysts and sensors - Suprity Shyam; Minisrang Daimary; Mahesh Narayan; Hemen Sarma (Next Materials, 2025)
Biochar-derived materials have emerged as sustainable and high-performance components in electroanalytical devices, owing to their large surface area, hierarchical porosity, chemical robustness, and renewability. This review highlights recent progress in employing biochar as both an electrocatalyst and electrode material, showcasing its superiority over traditional carbon-based alternatives in diverse applications such as energy storage, environmental monitoring, and electrochemical sensing. The intrinsic electrochemical properties of biochar-such as enhanced ion diffusion, redox kinetics, and charge storage-render it a promising candidate for use in supercapacitors, batteries, and fuel cells. However, native biochar often suffers from limited selectivity and moderate electrocatalytic activity. To address these limitations, researchers have increasingly modified biochar through functionalization and incorporation of advanced materials such as metal nanoparticles, conductive polymers, and transition metal oxides, significantly boosting its conductivity, analyte specificity, and overall electrochemical performance. Noteworthy advancements include N-doped biochar from pomelo peel exhibiting a specific capacitance of 391 F g⁻¹ and tri-modal porous carbon from shaddock endothelium reaching 550 F g⁻¹ with energy densities up to 46.88 Wh kg⁻¹. Biochar-based sensors have achieved ultra-low detection limits-for instance, 2 nM for bioactive molecules and 4.5 nM for heavy metal ions-while also demonstrating capabilities for multi-analyte pollutant detection and nitrate removal from groundwater. Additionally, biochar has shown high CO₂ adsorption capacities, outperforming commercial sorbents. The emergence of hybrid biochar composites and flexible, wearable devices marks a new direction in sustainable electrochemical technology. Overall, biochar is poised to play a transformative role in the development of next-generation electrocatalysts and sensors for green and scalable energy and environmental applications. Synopsis: Biochar is a promising material for energy conversion, storage, and for the development of sustainable catalysts with potential for commercialization and in green energy systems.